2020
DOI: 10.3389/fonc.2020.00479
|View full text |Cite
|
Sign up to set email alerts
|

Do Elderly Patients With Stage I–II Hepatocellular Carcinoma Benefit From More Radical Surgeries? A Population-Based Analysis

Abstract: Background and Aims: The best treatment modalities for elderly patients with stage I-II HCC (hepatocellular carcinoma) remain controversial in an era of a shortage of liver donors.Methods: From the SEER database (Surveillance, Epidemiology, and End Results program), 2,371 elderly patients were sampled as Cohort 1. OS (Overall Survival) and CSS (Cancer-Specific Survival) were compared between the Non-surgery and Surgery groups. A stratification analysis in a CSS Cox model was also conducted among sub-groups, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…With the improvement of surgical technology and perioperative management, the safety, feasibility, and availability of surgical resection for patients with stage I–II HCC have been widely improved ( 21 , 24 ). In terms of liver resection, our study showed that LR was not associated with better survival than WSR, which is similar to several previous studies ( 6 , 29 ). When determining whether a patient is eligible for surgical resection, one must consider tumor burden, liver function, presence of portal hypertension, and comorbidities, as well as the extent of hepatectomy and the expected volume of the future liver remnant.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…With the improvement of surgical technology and perioperative management, the safety, feasibility, and availability of surgical resection for patients with stage I–II HCC have been widely improved ( 21 , 24 ). In terms of liver resection, our study showed that LR was not associated with better survival than WSR, which is similar to several previous studies ( 6 , 29 ). When determining whether a patient is eligible for surgical resection, one must consider tumor burden, liver function, presence of portal hypertension, and comorbidities, as well as the extent of hepatectomy and the expected volume of the future liver remnant.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the nodal points of the research interval were also very significant. We ensured that more balanced and rational data were available by choosing from those methods ( 6 , 14 ). Moreover, we conducted subgroup analysis and performed an interaction test to eliminate variables that affected the relationship between surgical therapy and patients’ survival.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations